The Institutional Foundations of Religious Politics: Evidence from Indonesia. Issue 2 (23rd December 2019) - Bazzi, Samuel; Koehler-Derrick, Gabriel; Marx, Benjamin
Abstract: This article explores the foundations of religious influence in politics and society. We show that an important Islamic institution fostered the entrenchment of Islamism at a critical juncture in Indonesia, the world's largest Muslim country. In the early 1960s, rural elites transferred large amounts of land into waqf —inalienable charitable trusts in Islamic law—to avoid expropriation by the state. Regions facing a greater threat of expropriation exhibit more prevalent waqf land and Islamic institutions endowed as such, including mosques and religious schools. These endowments provided conservative forces with the capital needed to promote Islamist ideology and mobilize against the secular state. We identify lasting effects of the transfers on the size of the religious sector, electoral support for Islamist parties, and the adoption of local sharia laws. These effects are shaped by greater demand for religion in government but not by greater piety among the electorate. Waqf assets also impose costs on the local economy, particularly in agriculture, where these endowments are associated with lower productivity. Overall, our findings shed new light on the origins and consequences of Islamism.